Effect of thickness on fluorescence of resin-composites and dental substrates - Tavares, Carla; Tavares, Luiza; Correia, Ayla; Bresciani, Eduardo; Caneppele, Taciana (Brazilian Dental Science, 2016)
Objective: This study evaluated the effect of thickness on fluorescence of resin composites and tooth substrates (enamel and dentin). Material and methods: Ninety bovine incisors were used, resulting in 45 dentin and 45 enamel disks (6 mm diameter and 0.5, 1, or 1.5 mm in thickness). Ninety discs of Charisma, Filtek Z350 and IPS Empress Direct (for enamel and dentin) resins at same dimensions were built. Fluorescence measurements were performed using a fluorescence spectrophotometer (RF-5301PC, Shimadzu Corp) with excitation at 365 nm. Data were submitted to 2-way ANOVA and Tukey’s post hoc tests (? = 0.05). Results: The 2- way - ANOVA revealed statistically significant differences for all factors, as well as the interaction between them (p <0.05). Dentin specimens (1.5 mm) showed highest fluorescence (128.33 A.U.), while Filtek Z350 (dentin - 1.0 mm) showed the lowest fluorescence (29.84 A.U.). Thickness influenced fluorescence values of enamel substrate. Conclusion: The thickness influenced fluorescence of enamel and all resin composite assessed showed fluorescence lower than natural dentin. Keywords Dental enamel; Dental resins; Dentin; Spectrometry, Fluorescence.